The “Consulting Detective” Nithan Thong-in by King Vajiravudh - Waters, Tony (The Journal of the Siam Society, 2024)
This short study explores detective stories by Crown Prince Vajiravudh, later King Rama VI, in early 20th-century Siam. Compiled in Nithan Thong-in, these tales provide insights into Siamese society, culture, and history. Despite multiple reprints, an English translation is currently unavailable. This notice introduces the cultural richness of Mr Thong-in’s adventures, along with brief summaries of each story.